Plasmodium falciparum-infected erythrocytes: agglutination by diverse Kenyan plasma is associated with severe disease and young host age. - Bull, P; Kortok, M; Kai, O; Ndungu, F; Ross, A; Lowe, B; Newbold, C; Marsh, K (2000)
The variant surface antigens (VSAs) of Plasmodium falciparum-infected red blood cells are potentially important targets of naturally acquired immunity to malaria. Natural infections induce agglutinating antibodies specific to the VSA variants expressed by the infecting parasites. Previously, when different parasite isolates were tested against a panel of heterologous plasma from Kenyan children, the proportion of plasma that agglutinated the parasites (the agglutination frequency [AF]) was highly variable among isolates, suggesting the existence of rare and prevalent variants. Here, the AF of 115 isolates from Kenyan children were compared. The results show that the AF of isolates causing severe malaria were significantly higher than those of isolates causing mild malaria; and AF decreased significantly with the increasing age of the infected child. We propose that parasites causing severe disease tend to express a subset of VSA variants that are preferentially associated with infections of children with low immunity.